Developing Children's Learning Experiences: Analysis of John Locke's Empiricism Theory in the Perspective of Islamic Education - Kunthi, Yulianisa Dewi; Suwendi, Suwendi (J-PAI: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze John Locke's theory of empiricism from the perspective of Islamic education in enhancing children's learning experiences. Based on the context of Islamic education, it is an effort to guide humanity in living life following Islamic teachings. This requires an integrative view of how the Islamic context views this theory of empiricism in developing children's learning experiences so that there are implications for the current Islamic education process. The research employs a library research method with a qualitative approach. The materials used include literature from books and journal articles, particularly scientific journals published in the last five years, both national and international. The collected data is then processed and analyzed qualitatively to provide answers to the focus of this study. The results reveal that human knowledge derives from sensory experiences. Furthermore, Locke stated that humans are born in a blank state, like white paper, and the environment will give the graffiti what it will look like. Empiricism positions Ratio, or human reason, as the only function of processing the experience obtained from the environment into knowledge. However, knowledge acquisition is not solely based on experience in Islamic education. Instead, there are four ways for humans to acquire knowledge: sensory perception, the process of rational thought, and heart intuition through revelation. Additionally, Islam highlights that humans are born into the world already in a state of fitrah. This has implications for the Islamic education process, such as the role of teachers, religious experience, and the formation of children’s character.